2012
DOI: 10.1371/annotation/aac1c73d-b014-4cee-8dbc-eb8472de211d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Peptidoglycan-Modifying Enzyme Pgp1 Is Required for Helical Cell Shape and Pathogenicity Traits in Campylobacter jejuni

Abstract: The impact of bacterial morphology on virulence and transmission attributes of pathogens is poorly understood. The prevalent enteric pathogen Campylobacter jejuni displays a helical shape postulated as important for colonization and host interactions. However, this had not previously been demonstrated experimentally. C. jejuni is thus a good organism for exploring the role of factors modulating helical morphology on pathogenesis. We identified an uncharacterized gene, designated pgp1 (peptidoglycan peptidase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Recent studies reported that during oxidative stress conditions, C. jejuni transformed its spiral shape to a coccoid one [81]. Although we did not evaluate the morphological state of the internalized C. jejuni, decreased expression of pgp1 and pgp2 [13,111], two genes contributing to the helical cell shape, suggested that the bacterium lost its curved shape in the vacuole. In the rod shape formation, there is increased expression of penicillin-binding protein genes (pbp) [71,112], supporting our findings as elevated expression levels of pbpA, pbpB, and pbpC in the internalized C. jejuni following 3 h of internalisation were detected ( Supplementary Table S2C).…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies reported that during oxidative stress conditions, C. jejuni transformed its spiral shape to a coccoid one [81]. Although we did not evaluate the morphological state of the internalized C. jejuni, decreased expression of pgp1 and pgp2 [13,111], two genes contributing to the helical cell shape, suggested that the bacterium lost its curved shape in the vacuole. In the rod shape formation, there is increased expression of penicillin-binding protein genes (pbp) [71,112], supporting our findings as elevated expression levels of pbpA, pbpB, and pbpC in the internalized C. jejuni following 3 h of internalisation were detected ( Supplementary Table S2C).…”
Section: Discussionmentioning
confidence: 79%
“…The substrate of Csd4, mDAP-containing muramyltripeptide, is an agonist for the cytosolic innate immune receptor Nod1 (Girardin et al, 2003;Chamaillard et al, 2003), and thus a decreased amount of muramyltripeptide as a result of catalysis by Csd4 is likely to affect Nod1 activation and ultimately NF-B activity. Ápgp1, the mutant of the Csd4 homologue in C. jejuni, produces a significantly higher interleukin-8 (IL-8) response in human epithelial cells (INT407) than does wild-type C. jejuni (Frirdich et al, 2012;Sycuro et al, 2012), even though the Ácsd4 mutant is comparable to wildtype H. pylori in pro-inflammatory cytokine induction of gastric epithelial AGS cells (Sycuro et al, 2012). Therefore, it is suggested that d,l-carboxypeptidation by Csd4 homologues could affect the overall amount of released mDAP-containing muramyltripeptides, affect the helical shape and influence immune detection (Frirdich et al, 2012;Wyckoff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…3), but is absent in other CPases with known structures. Interestingly, Csd4 homologues are mainly found in spiral-shaped bacteria (Sycuro et al, 2012;Frirdich et al, 2012). Next, the CPase domain (Met22-Asn267) of H. pylori Csd4 shows relatively large r.m.s.…”
Section: Unique Features Of the Csd4 Dl-carboxypeptidase Domainmentioning
confidence: 99%
See 2 more Smart Citations